Pharmacological Effects of Hyaluronic Acid on Osteoarthritis of Knee Joint (TAJ: Journal of Teachers Association, 2022)
This longitudinal type of prospective study was carried out the clinical outcome of intra-articular Hyaluronic Acid injection in the management of mild to moderate osteoarthritis of knee joint. The sample size was 78 which was selected purposively. Partially structured questionnaire was used to collect data from the respondents by face-to-face interview. All efforts were made to collect data accurately. For open questions, the respondents were asked in such a manner way so that they could speak freely and explain their opinion in a normal and neutral way. Regarding age in group distribution of the respondents it was found that majority (47.4%) were in the age group of more than 61 years. The man monthly family income was 215431.21 ± 16898.112 Taka. About 41.0% were overweight, 14.1% had hypertension, 80.8% had multiple symptoms of osteoarthritis in knee joint, 94.87% had restricted range of motion. It was identified that 92.31% relieved pain by injections, 60.25% had satisfactory feeling after injections. The relationship between age group of the respondents was statistically significant (p